Application of blooms taxonomy of verbs to evaluate the cognitive domain in undergraduate medical physiology question papers: a critique - Kalasuramath, Suneeta; Tandon, Mayank; Deshpande, D. V.; Kumar, Vinod (International Journal of Research in Medical Sciences, 2017)
Background: Over the years medical education has evolved in the system of education, teaching and evaluation. It is the evaluation system that has the most insightful impact on learning. This study aimed to assess the use of taxonomy of verbs in medical physiology question papers as a tool for written examination for summative evaluation of I year medical students. Methods: Retrospective analysis of I MBBS undergraduate question papers of revised scheme Rajiv Gandhi University of health sciences, Bangalore from the year 2006- 2014 was done. Questions were analyzed individually for the use of taxonomy of verbs in each question, marks allotted for each, and type of cognition analyzed from each question. The data was classified using a modification of Bloom’s hierarchy of cognitive learning (level I, II, III). Results: Majority (45%) of the questions in the papers had no use of verbs. There was variability in the distribution of marks on various chapters of Physiology across the years. Comprehension and knowledge component of the cognitive domain were maximally assessed in the written examination. Conclusions: Examination and evaluation though a source of anxiety for the undergraduate medical students, it is essential to stimulate their cognitive skills by teaching and enhance the evaluation of mental and reasoning skills. It could be more facilitated by proper framing of questions by adequate usage of verbs.